New-age tourism students’ learning preferences and implications for tourism education at universities of technology - Mokoena, Pavla Phitlhelelo (Cape Peninsula University of Technology, 2022)
Discourse on the transformation of higher education from a consumption value point to an indication that Generation Z university students are the most affected by the education transformation process. Shifts in teaching practices and learning environments make it a constant challenge to understand the gap between tested and unknown pedagogical practices in tourism departments at Universities of Technology (UoTs) in South Africa. The Covid-19 pandemic has added to factors that impact on teaching and learning activities. Universities have gone to great lengths to respond to challenges brought about by the pandemic to provide facilities and resources for students during remote learning. The Covid-19 emergency implementation plans, referenced as ERT, implemented by the Council on Higher Education, were effected with clear guidelines of strategic goals that needed to be achieved to complete the academic agenda during the pandemic. Insights into students’ perceptions and learning experiences during this period might assist in revealing gaps between what students experienced and what educational leaders assume as critical factors for blended/hybrid learning. The aim of the study was to explore learning preferences of Tourism Management students at selected UoTs in the interest of engaging in learning, determining engagement within the various learning environments and ascertaining whether the Covid-19 pandemic had any impact on students’ learning preferences. Research on students’ experiences and perceptions during this period highlighted glaring challenges related to remote learning and provided deeper understanding of students’ study practices. The pragmatic approach of the study allowed for navigation of the research process at a time the impact of the Covid-19 pandemic was heavily felt. A questionnaire surveys involving N=147 online participating students at three UoTs was followed by two focus group interviews with N=8 participants using an explanatory-sequential research approach. The results indicated a significant preference for contact classes as opposed to remote classes p = .0098. The kinaesthetic learning style was the most preferred in the classroom (45%), with students indicating a need for activate-participatory face-to-face sessions, while the diverger learning style was the most preferred remote learning approach. In line with the survey results, all focus group interviewees/respondents professed conducting research on new content before either attending class or discussing elements they did not understand with peers to cement learning. Challenges experienced during remote learning were linked to issues of connectivity for access to learning, lack of social interaction leading to impacts on students’ mental wellbeing and resulting in a further widening gap to education access and success. Blended/hybrid learning is a possible standard for HE teaching and learning practices in South Africa. It is hoped tourism departments, institutions and government would consider recommendations of the study as long-term strategies that could include partnerships with all critical stakeholders, according to the ERT principles, in addition to the proposed student-focused framework guidelines presented for successful implementation of chosen blended/hybrid models.
Thesis (DTech (Tourism and Hospitality Management))--Cape Peninsula University of Technology, 2022
Keywords: COVID-19 Pandemic, 2020; Tourism -- Study and teaching (Higher); Tourism -- Vocational guidance; Hybrid learning; Educational innovations; Emergency management